Esthetic rehabilitation of anterior primary teeth using polyethylene fiber with two different approaches - M Jain; S Singla; BAK Bhushan; S Kumar; A Bhushan (Wolters Kluwer Medknow Publications, 2011)
An acceptable treatment approach for early childhood caries in the past may not necessarily be the best treatment option for our young patients today. Technological advances in dental materials and the approach to their use need to be considered, and the introduction of new adhesive systems, restorative materials, and the approach toward treating these teeth has yielded convincing results. Two such clinical case reports where polyethylene fibers were used as intra-canal posts and to splint the pontic fabricated with polyethylene fibers reinforced composite are reported.